The Relationship between Levels of Irrational Beliefs and Psychological Distress by Secondary School Teachers in Kiambu County, Kenya - Gakinya, Grace; Wasanga, Christine; Kipnusu, Robert (African Journal of Education and Practice, 2024)
Purpose: This study sought to “establish the relationship between levels of irrational beliefs and psychological distress by secondary school teachers in Kiambu County, Kenya Methodology: This study used a quasi-experimental research design. This study was carried out among selected teachers in secondary schools in Kiambu County. Kiambu County has a total of 303 secondary schools with a population of 3,617 teachers (County Government of Kiambu12 sub counties, however the target population will be the teachers in Thika town Sub County. Multistage sampling technique was used at three levels; sampling stage level one was used for selecting the schools at county level where Thika town Sub County was selected. The final overall sample size of 120. The study used the Depression, Anxiety and Stress Scale - 21 Items (DASS-21). Data was collected using questionnaire. Statistical Package for Social Sciences (SPSS) version 21 was used to analyse the data. Data was presented in form of tables. Findings: The results revealed that majority of the respondents (78.5%) had a moderate demandingness level. For Low Frustration Tolerance, majority of the respondents (72.9%) had a moderate Low Frustration Tolerance level. For awfulizing, majority of the respondents (86.9%) had moderate levels of awfulizing. For depreciation, majority of the respondents (54.2%) had moderate depreciation levels. The results also indicated that correlation analysis showed a moderately positive correlation coefficient (r) of 0.222, with p<0.05. This suggested that there is a statistically significant positive relationship between levels of Irrational Beliefs and Psychological Distress. Unique Contribution to Theory, Practice and Policy: The study used the Cognitive Behavioral Therapy approach. Schools and educational authorities should establish support systems for teachers experiencing psychological distress. This may include providing access to counseling services, peer support groups, or employee assistance programs aimed at addressing mental health concerns in the workplace.